Thang đo trách nhiệm xã hội của khách sạn theo cách tiếp cận khách hàng - Lê Văn, Huy; Nguyễn Hữu Thái, Thịnh; Trần Thị Thu, Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Understanding customer perception of corporate social responsibility (CSR) helps hotels design effective and appropriate CSR programs. With an exploratory sequential mixed-method, the study has developed the CSR scale in the hotel context according to the customer perception approach. It also establishes the predictive power of the CSR scale by examining its relationship with an expected outcome, i.e. tourist loyalty. A convenience sampling technique was used, a survey of 948 tourists who had stayed at 4–5 star hotels in Ho Chi Minh city, Khanh Hoa Province, Da Nang City, Quang Nam Province, and Hanoi capital. The study results confirmed that the Hotel CSR scale consists of 19 items with 4 dimensions, including (i) social CSR, (ii) economic CSR, (iii) stakeholder CSR, and (iv) environmental CSR. This Hotel CSR scale will be an important reference source for hotels to design and practice CSR in sustainable business operations.
Keywords: Social Responsibility; Hotel; Environment; Stakeholder; Sustainability